Derivation of irrigation requirements for radiological impact assessments - Almahayni, Talal; Crout, Neil M.J. (Elsevier, 2016)
When assessing the radiological impacts of radioactive waste disposal, irrigation using groundwater contaminated with releases from the disposal system is a principal means of crop and soil contamination. In spite of their importance for radiological impact assessments, irrigation data are scarce and often associated with considerable uncertainty for several reasons including limited obligation to measure groundwater abstraction and differences in measuring methodologies. Further uncertainty arises from environmental (e.g. climate and landscape) change likely to occur during the assessment long time frame.